CGIAR and Partners Exhibition Day - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
CGIAR and Partners Exhibition Day: This day is all about featuring the work, especially innovations, from CGIAR and will put a spotlight on the work done by various CGIAR centers including a presentation of the various technologies and innovations. The media are invited to the event and will include multiple interviews to highlight CGIAR’s work.